3(z-4)=4(3-z)

Simple and best practice solution for 3(z-4)=4(3-z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(z-4)=4(3-z) equation:



3(z-4)=4(3-z)
We move all terms to the left:
3(z-4)-(4(3-z))=0
We add all the numbers together, and all the variables
3(z-4)-(4(-1z+3))=0
We multiply parentheses
3z-(4(-1z+3))-12=0
We calculate terms in parentheses: -(4(-1z+3)), so:
4(-1z+3)
We multiply parentheses
-4z+12
Back to the equation:
-(-4z+12)
We get rid of parentheses
3z+4z-12-12=0
We add all the numbers together, and all the variables
7z-24=0
We move all terms containing z to the left, all other terms to the right
7z=24
z=24/7
z=3+3/7

See similar equations:

| 9x5=270 | | 12,6x+5,8=9x-4,3 | | 2(-6n+5)=4n+2(1-6n) | | 6/5x=-3 | | X+6y-3=0 | | a=-2+18 | | (-x-8)=45 | | 1z+109+1z+89=180 | | 38+7k=8(k+40) | | 0.75a+4=0.25a+11 | | 38+7k=8(k+40 | | 15+p/3=12 | | (3x-18)+(2x-1)=x | | -6x+3=3x+111 | | -11/13=x+1/13 | | 6x-31-20x=3-(10-4X) | | 3/10+c=11/15 | | 6-7x+x2=0 | | 6x-31-20x=3-(10-4X0 | | 5x+40=11x-60 | | 11+n/11=2 | | 8h^2+9h-575=0 | | 3(16)+29=x | | 5(16)+23=x | | 4y-7+2y=-3y=-3y-1 | | 5x+4=15+4x | | 7/5+3/5x=38/15+4/3x+1/3 | | 4v+2(8-8v)=40-4v | | 3(16)+2=x | | 2+8y=24 | | 2^(n+4)-2^(n+2)=3 | | 3(p+2)-7=18 |

Equations solver categories